INFORMATION-BASED CONFLICT IN AFRICA - Van Niekerk, Brett; Maharaj, Manoj S (Scientia Militaria - South African Journal of Military Studies, 2013)
For a long time, the African continent was regarded as the ‘Dark Continent’. The rapid assimilation of information technologies into the African economies has placed Africa firmly on a trajectory that will see it compete and integrate with the developed world. As nations and organisations become more information-centric, it is natural that conflicts and competition amongst the various nations or organisations will become increasingly information-based. In this article, the authors reflect upon information-based conflict in Africa. Areas of information conflict that are discussed include censorship, communications intercepts, the use of information and communications to instigate violence and uprisings, and the possibility of cyberwarfare. The article shows that the use of technology to conduct information conflict in Africa is prevalent, and that it is likely to increase.